2019
DOI: 10.1128/aac.02492-18
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of the Drug Interaction Potential of Doravirine

Abstract: Doravirine is a novel nonnucleoside reverse transcriptase inhibitor for the treatment of human immunodeficiency virus type 1 infection. In vitro studies were conducted to assess the potential for drug interactions with doravirine via major drug-metabolizing enzymes and transporters. Kinetic studies confirmed that cytochrome P450 3A (CYP3A) plays a major role in the metabolism of doravirine, with ϳ20-fold-higher catalytic efficiency for CYP3A4 versus CYP3A5. Doravirine was not a substrate of breast cancer resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(61 citation statements)
references
References 29 publications
(44 reference statements)
9
52
0
Order By: Relevance
“…22 Indeed, in this study, no stereospecific interactions between doravirine and methadone were observed, as R-, S-, and total methadone PK were not affected by coadministration of doravirine, and similar values for AUC 0-24 , C max , and C 24 were observed in both the presence and absence of doravirine. As doravirine may be administered to people living with HIV on methadone maintenance therapy, a trial was conducted to assess a potential PK interaction.…”
Section: Discussionmentioning
confidence: 44%
See 4 more Smart Citations
“…22 Indeed, in this study, no stereospecific interactions between doravirine and methadone were observed, as R-, S-, and total methadone PK were not affected by coadministration of doravirine, and similar values for AUC 0-24 , C max , and C 24 were observed in both the presence and absence of doravirine. As doravirine may be administered to people living with HIV on methadone maintenance therapy, a trial was conducted to assess a potential PK interaction.…”
Section: Discussionmentioning
confidence: 44%
“…10 In one study, the half-life of the R-and S-forms of methadone was reported to be 37.5 and 28.6 hours, respectively. 14,15 To date, preclinical and clinical data suggest that doravirine has minimal drug-drug interactions (DDIs) [18][19][20][21][22] as doravirine is not expected to either induce or inhibit any of the major CYP enzymes or transporters. 14,15 Phase 2 and 3 trials in treatment-naïve HIV-1-infected adults have shown that doravirine in combination with other antiretroviral agents is noninferior in terms of efficacy, but also demonstrates a more favorable safety profile compared with other treatment regimens.…”
mentioning
confidence: 99%
See 3 more Smart Citations